Dendrobium officinale Flower Extraction Mitigates Alcohol-Induced Liver Injury in Mice: Role of Antisteatosis, Antioxidative, and Anti-Inflammatory. (23rd October 2020) - Wu, Yu-Lin; Huang, Si-Han; He, Chun-Mei; Qiu, Bo; Liu, Jing-Jing; Li, Jia; Lin, Ying; Yu, Sheng-Lu; Wang, Hong-Feng; Zhang, Gui-Fang
Abstract : The study aimed to evaluate the protective effect of Dendrobium officinale flower extraction (DOFE) on alcohol-induced liver injury and its probable mechanisms in mice. The chemical composition of DOFE was performed via UPLC/MS. Male Kunming mice were used to establish alcohol-induced liver injury models by oral gavage of 56% alcohol. Results showed that DOFE dramatically attenuated the increased serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), and triacylglycerol (TG). Meanwhile, hematoxylin and eosin and Oil Red O staining showed that DOFE attenuated degeneration, inflammatory infiltration, and lipid droplet accumulation. DOFE was also found to suppress the activity of malonaldehyde (MDA) and enhanced the level of glutathione (GSH) and the activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) in the liver. The protection of DOFE against oxidative stress was associated with the downregulation of hepatic cytochrome P450 2E1 (CYP2E1) and upregulation of nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), and NAD(P)H quinone oxidoreductase l (NQO1). Additionally, DOFE suppressed inflammation via downregulating Toll-like receptor-4 (TLR-4) and nuclear factor kappa-B P65 (NF- κ B P65). Thus, DOFE exhibited a significant protective effect against alcohol-induced liver injury through its antisteatosis, antioxidative, and anti-inflammatory effect.